TREATMENT OF VAGINAL DYSBIOTIC DISORDERS IN PREGNANT WOMEN BEFORE CHILDBIRTH - Yuldasheva Farangiz Ismatiloevna (Scholar Express Journals, 2022)
Infectious and inflammatory diseases of the female genital organs caused by various pathogens are a serious problem in obstetrics and gynecology [1]. In addition, violations of vaginal microbiocenosis during pregnancy are of particular importance in obstetric practice, since changes in the vaginal microflora lead to a complicated course of pregnancy, childbirth and the postpartum period, as well as to the development of infectious and inflammatory processes in the mother and fetus [2, 3].In recent years, an increase in vaginal infections has been noted in many countries of the world, which occupy a leading place in the structure of obstetric and gynecological morbidity. The introduction of modern technologies in clinical microbiology makes it possible to expand research and show that the negative effect on the microflora of a macroorganism of various localization, including the vagina, leads to a variety of pathologies of both inflammatory and non-inflammatory genesis [1,3].
Keywords: pregnancy; vaginal dysbiosis; vaginal infection; violation of microflora